Liver transplantation for fibrolamellar hepatocellular carcinoma: A national perspective. Issue 3 (23rd November 2016) - Atienza, Leonardo Garcia; Berger, Jonathan; Mei, Xiaonan; Shah, Malay B.; Daily, Michael F.; Grigorian, Alla; Gedaly, Roberto
Abstract : Background: Fibrolamellar Hepatocellular Carcinoma (FL‐HCC) is a rare primary liver tumor that usually presents in younger patients without underlying liver disease. Methods: We queried the United Network of Organ Sharing (UNOS) database between October 1988 and January 2013 to evaluate outcomes in patients with FL‐HCC undergoing liver transplantation in the United States compared to patients with conventional Hepatocellular Carcinoma (HCC). Results: Sixty‐three patients were identified (57% female, mean age 30 years). Only one patient (2%) had an associated Hepatitis C Virus. Mean Model for End‐Stage Liver Disease (MELD) score at the time of transplantation was 11.3. Mean waiting time was 325 days and mean cold ischemic time was 6 hr. Overall survival of FL‐HCC patients at 1, 3, and 5 years was 96%, 80%, and 48% as compared to HCC patients whose rates were 89%, 77%, and 68%. Six patients had tumor recurrence (10%). The Cox Model demonstrated that MELD and cold ischemic time are the strongest predictors of overall survival in FL‐HCC patients. Age and wait time were not associated with poor patient survival in this series. Conclusions: Good results can be obtained in selected patients transplanted for FL‐HCC. FL‐HCC patients had similar survival compared to those transplanted for HCC. J. Surg. Oncol. 2017;115:319–323 . © 2016 Wiley Periodicals, Inc.